Democrazia fiscale e finanziamento delle religioni. Le campagne pubblicitarie per l’8xmille della Chiesa cattolica: dalla rendicontazione alla promozione (Stato, Chiese e pluralismo confessionale, 2024)
Fiscal democracy and the financing of religions. The advertising campaigns for the Catholic Church's 8xmille: from reporting to promotionABSTRACT: On the eve of the fortieth anniversary of the law (No. 222 of 1985) that introduced a new regulatory framework for the Catholic Church's financial system, which was subsequently extended to other religious groups, presents an opportunity to reflect on the significance and utility of the revisions introduced from the Villa Madama Agreement and to evaluate the ongoing critical issues raised by doctrinal and legal developments in light of recent developments. In the present era, while some doubts appear to have reached a state of equilibrium with regard to the stability of the data, others have the effect of introducing a certain degree of uncertainty. An analysis of the issues pertaining to advertising and reporting reveals a tendency on the part of the Catholic Church to focus less on the primary driver of change, namely the sustenance of the clergy, and instead direct attention towards welfare interventions that bear resemblance to those typically undertaken by Third Sector entities. The persistence of old doubts and the emergence of new challenges, it is pertinent to assess whether the consolidated 8xmille mechanism remains a viable and effective response to the prevailing circumstances.SOMMARIO: 1. I (quasi) quarant’anni dell’8xmille - 2. Il sistema di finanziamento pubblico della Chiesa cattolica. Un prima e un dopo - 3. Come funziona l’8xmille? Le aporie di un sistema tra punti di forza e punti di debolezza - 4. “Dati alla mano”. La rendicontazione CEI 2023 - 5. Diritto, religioni e pubblicità - 6. Gli spot 8xmille - 7. Quale futuro per il finanziamento delle religioni?